1998
DOI: 10.1007/s001470050491
|View full text |Cite
|
Sign up to set email alerts
|

Reflex sympathetic dystrophy of the lower limbs after kidney transplantation

Abstract: Reflex sympathetic dystrophy syndrome (RSDS) is a rarely described complication after different types of organ transplants. Three out of 147 kidney recipients treated at our center during the last 6 years developed severe bilateral symmetrical pain in the ankles and knees, with great difficulties in walking 2-3 months after kidney transplantation. Clinical examination revealed periarticular soft tissue swelling and vasomotor changes with no effusion. Patchy osteoporotic patterns were seen radiographically in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…The authors of three articles reported the occurrence of RSD in the lower extremities in patients after renal transplantation. A total of seven patients had severe pain in one or both of the knees and ankles; clinical examination revealed increased local temperature, trophic changes and periarticular soft tissue swelling (Grandtnerova et al., ; Puig i Mari et al., ; Molina et al., ). Table shows the number and percentage of reported eliciting factors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors of three articles reported the occurrence of RSD in the lower extremities in patients after renal transplantation. A total of seven patients had severe pain in one or both of the knees and ankles; clinical examination revealed increased local temperature, trophic changes and periarticular soft tissue swelling (Grandtnerova et al., ; Puig i Mari et al., ; Molina et al., ). Table shows the number and percentage of reported eliciting factors.…”
Section: Resultsmentioning
confidence: 99%
“…In all patients who developed RSD or CRPS after renal transplantation, radiographs showed patchy osteopenia and bone scintigraphy showed increased uptake in the affected areas; the authors considered these findings as supportive in diagnosing RSD or CRPS (Grandtnerova et al, 1998;Puig i Mari et al, 2000;Molina et al, 2008).…”
Section: Radiographs/bone Scansmentioning
confidence: 99%
“…In 1998 Grandtnerova et al 12 and Pilmore et al, 13 described more cases of pain arising 2-3 months after renal transplant. In 1999 Torregrosa and Campistol 7 published a review on post-transplant RSDS in patients treated with cyclosporine, with a prevalence between 1 and 10%.…”
Section: Discussionmentioning
confidence: 99%
“…The pain associated with CIPS is typically symmetrical, sharp, stinging and intermittent and increases when standing or walking (Grotz et al 2001; Kida et al 2004; Collini et al 2006; Fujii et al 2006; Noda et al 2008). Although CIPS seems to affect about 5–10% of patients who undergo kidney, heart, lung, liver, pancreas, or bone marrow transplantation, it is probably much more common in transplant patients because CIPS is frequently diagnosed as reflex sympathetic dystrophy syndrome (Muñoz‐Gomez et al 1991; Grandtnerova et al 1998; Puig et al 2000; Ybarra et al 2003). Also, the concurrent use of L‐type Ca 2+ channel blockers (to treat hypertension caused by calcineurin inhibitors) may mask CIPS in many patients, because L‐type Ca 2+ channels contribute to regulating glutamatergic input from primary afferents to the spinal dorsal horn (Bao et al 1998).…”
Section: Introductionmentioning
confidence: 99%